Paving the last mile with glass. - Green, P.E., Jr.
Each year, the local phone companies (more properly known as ILECs, for incumbent local exchange carriers) replace 3-4 percent of their copper twisted-pair subscriber lines because of physical deterioration. They also add 1.5 million lines annually to newly built homes. But by largely ignoring the opportunity to use fiber for these installations, they are putting their very survival at risk. The future does in fact belong to fiber-based high-performance broadband (plus wireless for lower bit rates and shorter distances), and if the telephone companies don't provide it, the cable companies will drive them to the wall. In their aggressive long-range game, cable companies are wiring as many homes as possible, first with TV and then with cable-modem service. Then they can easily add telephone service, connecting to the public-switched telephone network via the ILECs' central offices. Before long, thanks to the high bandwidth of coaxial cable, they will also begin pushing high-definition television on the shorter links, strengthening their position as the home portal of choice. It's hard to see how the ILECs will be able to match these offerings with their copper twisted pairs.
Keywords: Cable companies; Cable-modem service; Coaxial cable; Copper twisted-pair subscriber lines; Fiber-based high-performance broadband; Incumbent local exchange carriers; Local phone companies; Optical fiber; Public switched telephone network; Telephone companies; Telephone service